Regulação de tensão em redes elétricas utilizando sistemas de armazenamento de energia em baterias - Chrystiano Alves Galdino (2023)
With the increasing penetration of Distributed Generation (DG), concerns related to voltage regulation in electrical grid arise. This work presents a control strategy to command the injection of active and reactive power in distribution grids, performing voltage regulation through Battery Energy Storage Systems (BESS). Among the various existing strategies for this problem, one that uses a modified Droop control was chosen, seeking to meet the need to provide capacitive or inductive reactive power to control the voltage at the connection point. Computer simulations are carried out using the PLECS software, for the development of the control strategy and to verify the behavior of the system under analysis. A 2 MW BESS is considered for the computational study, connected to an IEEE three-phase test network, which has 13 buses interconnected through distribution lines and unbalanced loads. With the proof through simulations, experimental tests were carried out using a prototype of a 12 kW BESS connected to a regenerative grid emulator, whose objective is to emulate the characteristics of the electrical network. Based on the results obtained by computational and experimental analysis, the voltage regulation capacity was evaluated through the use of BESS in distribution networks.